A measurement to driving situation awareness in signalized intersections. (July 2018) - Mao, Yan; Wang, Wuhong; Ding, Chenxi; Guo, Weiwei; Jiang, Xiaobei; Baumann, Martin; Wets, Geert
Highlights: This study classified the left-turn drivers' performance into four types. A logistic regression model was used to obtain the critical gaps. The conservative drivers are more likely to reject the larger lags/gaps. The poor response execution may cause drivers to have difficulties. Abstract: Drivers get involved easily in Left-Turn Across Path with Opposite Direction Traffic (LTAP-OD) conflicts at signalized intersection with unprotected left-turn phasing. This study classified the left-turn drivers' performance into four types: (1) the correct acceptance of safe lags/gaps, (2) the correct rejection of dangerous lags/gaps, (3) the false rejection of safe lags/gaps and (4) the false acceptance of dangerous lags/gaps. Based on the high mounted video camera data, the logistic regression model was used to obtain the critical gaps for estimating whether the lags/gaps were safe or not. The results show that the cognition behavior of the left-turn drivers should be improved while the gap/lag is drawn near the critical gap. Furthermore, the conservative drivers are more likely to reject the larger lags/gaps and yield the right-of-way to the opposing vehicles. Simultaneously the poor response execution may cause drivers to have difficulties during the turning performance when the lags/gaps are large enough. These results could be used as the basis for a discussion of the right time to support the drivers.